Challenges And Importance Of Teaching Balance Exercises To Young Artistic Gymnasts (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
Present article is devoted to the how to use balance exercises to young artistic gymnastics. The main point of teaching methods of them and also specific balance exercises in order to improve their skills on it.